Business Model Development of a Fresh Milk Agro-Industry in Rural Areas - Hanik Atus Sangadah; Machfud Machfud; Elisa Anggraeni (School of Business, Bogor Agricultural University (SB-IPB), 2021)
This research aims to identify several business models of fresh milk agro-industry that are emerging in rural areas, as well as factors that influence agro-industry development, and establish a dairy agro-industry business model framework. The case study method used in this research consists of an agro-industry with business models and cooperatives. According to the finding of this research, there are seven supporting factors that influence the growth of the fresh milk agro-industry in rural areas, that are; (1) organizational structure, (2) fresh milk handling operations, (3) technology application for production activities, (4) training of employees and breeders, (5) product marketing strategies, (6) product quality and quality assurance, (7) company actor’s innovation. These seven factors can be determined using the weight ratio to assess the value of each factor that influences the development of the fresh milk agro-industry in rural areas, namely business management (0.2641), raw material handling (0.1510), and quality assurance (0.1347). The importance of the decision is a crucial factor in the development of the dairy agro-industry in rural areas. In rural areas, the fresh milk agro-industry business model is a cooperative form of business, as well as a business model that incorporates both private and cooperative business practices. The more varied the business models examined, the stronger the fresh milk agro-industrial business model system would be. Since they help small-scale milk farmers in rural areas market their products, regional milk cooperatives are still the best business model to use. Keywords: business model, BMC (Business Model Canvas), cross-case analysis, fresh milk agro-industry, multiple case study